Avaliação do tecido ósseo neoformado em alvéolos dentais de ratos espontaneamente hipertensos (SHR) pelo método densitométrico - Garcia, Lourdes Maria González [UNESP] (2009)
The healing of tooth extraction wounds may be altered by different pathologies. The objective of this study was to evaluate by Densitometry analysis the formation of bone tissue in wounds healing of tooth extraction of spontaneously hypertensive rats (SHR) in the periods between the 7th and the 42nd day after extraction. SHR with systolic arterial pressure higher than 150mmHg and normotensive Wistar rats with 110-112 mmHg, were used in the experiments (180-200g). The rats were anesthetized, the right upper incisor was removed and the wounds were sutured with surgical thread. The sacrifice was made at the 7th, 14th, 21st, 28th and 42nd days post-surgery. The pieces of the tooth socket were removed and radiographed with the X-ray instrument GE-100, with 50 kvp, 10 mA, 10 impulses, focus-film distance of 40 cm. The image obtained with plate optical system was analyzed by Digora software for Windows 1.51. The middle third (TM) and apical (TA) of the alveolar healing were evaluated. Bone mineral density (BMD) was expressed as the mean ± SEM of 5 animals per period analysis. The results were evaluated in the group by multivariate (ANOVA) and compared between groups by Student's t test. Results: In Wistar rats, it was observed an increase in BMD in alveolar healing comparing the 28th day to the 7th day in both the TM and TA. In alveolar healing of SHR, in the TA there were no significant differences between BMD in the different of periods. In the TM, there was no difference between the BMD values for 7th, 14th, 21st, 42nd days; however, on the 28th there was a reduction in BMD in relation to the values of the 21st day. We observed on the 21st and 42nd days, an increase on the BMD in the TM of alveolar healing in SHR when compared to rats Wistar. A reduction on the BMD 28th day was observed in the TM and TA in the tooth socket of SHR when compared to rats Wistar. Conclusion: The results suggest that the tooth wound...